A Prospective Study on the Effect of Sport Specialization on Lower Extremity Injury Rates in High School Athletes. (October 2017) - McGuine, Timothy A.; Post, Eric G.; Hetzel, Scott J.; Brooks, M. Alison; Trigsted, Stephanie; Bell, David R.
Background: Sport specialization is associated with an increased risk of musculoskeletal lower extremity injuries (LEIs) in adolescent athletes presenting in clinical settings. However, sport specialization and the incidence of LEIs have not been investigated prospectively in a large population of adolescent athletes. Purpose: To determine if sport specialization was associated with an increased risk of LEIs in high school athletes. Study Design: Cohort study; Level of evidence, 2. Methods: Participants (interscholastic athletes in grades 9-12) were recruited from 29 Wisconsin high schools during the 2015-2016 school year. Participants completed a questionnaire identifying their sport participation and history of LEIs. Sport specialization of low, moderate, or high was determined using a previously published 3-point scale. Athletic trainers reported all LEIs that occurred during the school year. Analyses included group proportions, odds ratios (ORs) and 95% CIs, and days lost due to injury (median and interquartile range [IQR]). Multivariate Cox proportional hazard ratios (HRs) with 95% CIs were calculated to investigate the association between the incidence of LEIs and sport specialization level. Results: A total of 1544 participants (50.5% female; mean age, 16.1 ± 1.1 years) enrolled in the study, competed in 2843 athletic seasons, and participated in 167, 349 athlete-exposures. Sport specialization was classified as low (59.5%), moderate (27.1%), or high (13.4%). Two hundred thirty-five participants (15.2%) sustained a total of 276 LEIs that caused them to miss a median of 7.0 days (IQR, 2.0-22.8). Injuries occurred most often to the ankle (34.4%), knee (25.0%), and upper leg (12.7%) and included ligament sprains (40.9%), muscle/tendon strains (25.4%), and tendinitis/tenosynovitis (19.6%). The incidence of LEIs for moderate participants was higher than for low participants (HR, 1.51 [95% CI, 1.04-2.20]; P = .03). The incidence of LEIs for high participants was higher than for low participants (HR, 1.85 [95% CI, 1.12-3.06]; P = .02). Conclusion: Athletes with moderate or high sport specialization were more likely to sustain an LEI than athletes with low specialization. Sports medicine providers need to educate coaches, parents, and interscholastic athletes regarding the increased risk of LEIs for athletes who specialize in a single sport.